Synthesis of some Thiadiazole and Azetidinone Derivatives as their Anti inflammatory Activities - Bhati, Sudhir Kumar (International Journal of Pharmaceutical & Biological Archive, 2015)
Synthesis of some Thiadiazole and Azetidinone Derivatives as their Anti inflammatory Activities